2001
DOI: 10.1348/135910701169034
|View full text |Cite
|
Sign up to set email alerts
|

Self‐efficacy and goal importance in the prediction of physical disability in people following hospitalization: A prospective study

Abstract: The findings demonstrate that recovery is governed not solely by medical phenomena but also by psychological variables and suggest that modification of these variables may have an impact on recovery outcomes. Moreover, attention should be paid to the timing of such intervention and to the length of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
3
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 27 publications
3
70
3
2
Order By: Relevance
“…Thus the present 8 study adds further support that goal importance or valence should be regarded as an important 9 variable in influencing goal progress. 10 The interaction in the present study also differed to that of Orbell et al (2001) findings. 11 Orbell et al found that high levels of self-efficacy had a strong impact upon progress in mobility 12 regardless of goal importance.…”
contrasting
confidence: 85%
“…Thus the present 8 study adds further support that goal importance or valence should be regarded as an important 9 variable in influencing goal progress. 10 The interaction in the present study also differed to that of Orbell et al (2001) findings. 11 Orbell et al found that high levels of self-efficacy had a strong impact upon progress in mobility 12 regardless of goal importance.…”
contrasting
confidence: 85%
“…For example, following stroke, perceived control over recovery predicted change in disability when controlling for impairment and other clinical variables (Johnston, Morrison, MacWalter & Partridge, 1999;Partridge & Johnston, 1989), and predicted recovery after three years (Johnston, Pollard, Morrison & MacWalter, 2004). Self-efficacy and perceived behavioral control (PBC) predicted disability and recovery from stroke six months after discharge (Bonetti & Johnston, 2008), and in orthopedic patients self-efficacy to perform activities of daily living predicted disability after joint replacement (Orbell, Johnston, Rowley, Davey & Espley, 2001). …”
Section: Impactmentioning
confidence: 99%
“…In general, studies indicate that higher SE for pain shares a positive relation with functional ability and adjustment to chronic pain [146][147][148], and mediates the relation between pain and disability [149], pain and depression [150], and life stress and headache [151]. Clinical investigations indicate that SE for pain is associated with lower pain intensity [148,152], and less severe pain-related distress and disability [95,153,154]. In prospective studies, SE predicts outcomes for post-surgical pain rehabilitation [144,155].…”
Section: Interventional Pain Medicine and Pain Beliefsmentioning
confidence: 99%